HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KEKUATAN OTOT PERUT DENGAN HASIL HEADING DALAM PERMAINAN SEPAKBOLA PADA BERLIN FC KECAMATAN KUALA CENAKU KABUPATEN INDRAGIRI HULU - hamzah hamzah (FKIP Universitas Islam Indragiri, 2017)
This study aims to determine the relationship of explosive muscle limb power and abdominal muscle strength with heading results in football games at Berlin FC Kuala Cenaku Sub-district Indragiri Hulu Regency. This type of research is correlation, where the correlation analysis to find the magnitude of influence or relationship between variables, independent variables (X1) and (X2) to the dependent variable (Y). The population in this study is the football player Berlin FC Kuala Cenaku Subdistrict Indragiri Hulu district, amounting to 15 people. Sedangan samples taken using the technique Total Sampling technique is the researchers take the entire football players who numbered 15 players. Data analysis technique used is with multiple product moment correlation. From result analyze data known that 1) result of correlation calculation (rx1y) relation of explosion muscle power of limb with result of heading in game of football equal to r count = 0,52> r table = 0,514. 2) The result of calculation of correlation of abdominal muscle strength relationship with heading result in football game equal to r count = 0,53> r table = 0,514. 3) The result of correlation of explosive power of leg muscle and abdominal muscle strength with heading result in game of football count = 0,62> r table = 0,514. Then the relationship between variables X1. X2 with variable Y is categorized significant, where the truth is tested with t-Test formula and obtained t arithmetic = 3.32> t table = 2.16. Thus Ho is rejected and Ha accepted.